Procedural fairness concerns in supply chain with retailer promotional effort. (14th May 2018) - Nie, Tengfei; Liu, Hualin; Dong, Yilun; Du, Shaofu
Abstract : Purpose: The existing literature has a lack of modeling of procedural fairness concerns in the supply chain level. This paper aims to investigate how procedural fairness concerns affect channel decisions, performance and coordination. Design/methodology/approach: This paper considers a supply chain consisting of one supplier and one retailer who have procedural fairness concerns in a classic Stackelberg game setting. The model is set in sales promotional environment. According to the existing literature, engagement is used to depict fair process. Some findings are made through analyzing respective decisions of the supplier and the retailer under the influence of procedural fairness concerns. Findings: The results show that the channel efficiency can be improved when the retailer exhibits procedural fairness concerns, but if the aversion to unfair process exceeds a certain threshold, the retailer cannot benefit from it. Besides, the retailer profits more when he cares about distributional fairness, although the whole channel surplus can be improved by procedural fairness concerns. Originality/value: This is the first paper to study the influences of procedural fairness concerns on supply chain decisions and channel performance. Finally, a mechanism combining a wholesale price contract with slotting allowances is proposed to coordinate the supply chain.